ORGANISATION AND MANAGEMENT ISSUES FOR ELECTRONIC JOURNALS: A BANGLADESH PERSPECTIVE - Islam, Md. Shiful; Chowdhury, Mohammed Abu Khaled (Malaysian Journal of Library and Information Science, 2006)
This article provides information about electronic journals (e-journals), their subscribers, management issues and necessities from the Bangladesh perspective. An attempt has been made to explore the infrastructural facilities and the existing problems of libraries and information centres that are subscribing to e-journals. The study also discusses the status of e-journal usage and accessibility in selected libraries and information centres, as well as advantages, limitations and prospects for e-journals in the context of this country. Finally the paper suggests that there is a need to establish a workable and sustainable consortium among libraries and information institutions in Bangladesh. It also recommends that systematic efforts should be made urgently for the proper organisation and management of e-journals.